Tren Penelitian Kesehatan Mental di Era Digital: Pendekatan Bibliometrik - Gunadi, Zarra Zakiyyah Izzaturrahmah; Anwar, Rully Khairul; Khadijah, Ute Lies Siti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
The presence of social media and various platforms in digital age had a huge impact on human mental health. Initially, it expands access to information about mental health and allows interaction with anyone, anywhere. However, overuse of social media can increase the risk of depression and anxiety due to comparison and competition among users. To protect well-being and mental health in the digital age, it’s important to strike a balance in using digital tools. More in-depth studies on mental health issues in the digital age are needed to provide insights and promote well-being. It’s also important to pay attention to related research trends to stay relevant. Bibliometric analysis methods were used to show growth patterns, highlight dominant areas of focus, and understand the knowledge dynamics of mental health research trends in the digital age over time. Using a quantitative and statistical approach, the results showed that the most productive author and source were Adrian Aguilera and JMIR Mental Health. The phrase 'pandemic' was the most cited. Research on this topic is mostly conducted on women and adolescents. Word cloud analysis shows the terms 'mental health', 'human', 'female' and 'adolescent' appear frequently in research titles. Recent topics include 'female', 'male', and 'risk factor', with the main focus on humans and mental health. While the most common research focus is on people and mental health itself.